Hydroformylation of 1-hexene catalyzed by nickel systems containing phosphines as ancillary ligand(Hydroformylation of 1-hexene with nickel systems): Hidroformilación de 1-hexeno catalizada por sistemas de níquel conteniendo fosfinas como ligandos espectadores(Hidroformilación de 1-hexeno con sistemas de níquel) - Rosales, Merlín; Lugo, Darwin; González, Ángel; Baricelli, Pablo (Ciencia, 2021)
In the present work, it was studied the hydroformylation of 1-hexene by using catalytic systems formed in situ by addition of triphenylphosphine to the nickel salt, NiCl2.6H2O, under mild reaction conditions (125 ºC and 50 atm syn-gas). The system that presented the highest catalytic activity was the one prepared by addition of 8 equivalents of triphenylphosphine to the nickel salt (Ni/8PPh3), obtaining a n/i ratio close to 3. The addition of amines produces the inhibition of this reaction. The systems containing bi- and tridentate phosphine showed to be inactive for this reaction. A coordination chemistry study allowed us to isolate and characterize the complex [Ni(CO)2(PPh3)2], which is proposed as the possible resting state for the hydroformylation reaction.